Hyperglycemia is associated with reduced testicular function and activin dysregulation in the Ins2Akita+/− mouse model of type 1 diabetes - Maresch, Constanze Christin; Hammes, Hans-Peter (Molecular and cellular endocrinology, 2017)
Type 1 diabetes (T1D) is associated with subfertility in men. We hypothesised that this results from inhibitory effects of chronic hyperglycemia on testicular function and used the Ins2Akita+/− mouse model to investigate this. Diabetic mice exhibited progressive testicular dysfunction, with a 30% reduction in testis weight at 24 weeks of age. Diabetic mice showed significantly reduced seminiferous tubule diameters and increased spermatogenic disruption, although testes morphology appeared grossly normal. Unexpectedly, serum LH and intra-testicular testosterone were similar in all groups. Ins2Akita+/− mice displayed elevation of the testicular inflammatory cytokines activin A and IL-6. Intratesticular activin B was downregulated, while the activin regulatory proteins, follistatin and inhibin, were unchanged. Activin signalling, measured by pSmad3 and Smad4 production, was enhanced in diabetic mice only. These results suggest that prolonged exposure to hyperglycemia in the Ins2Akita+/− mice leads to progressive testicular disruption mediated by testicular activin activity, rather than hormonal dysregulation.
Im Titel ist Akita+/- hochgestellt
Available online 16 February 2017
Gesehen am 01.10.2018